2000
DOI: 10.1046/j.1523-1755.2000.00930.x
|View full text |Cite
|
Sign up to set email alerts
|

Suppressive effects of fish oil on mesangial cell proliferation in vitro and in vivo

Abstract: Fish oil inhibits mesangial cell activation and proliferation in ATS glomerulonephritis, reduces proteinuria, and decreases histologic evidence of glomerular damage. In vitro, the antiproliferative effects of fish oil are more likely related to the action of DHA. We suggest that orally administered fish oil, or purified DHA, may have a suppressive effect in acute phases or relapses of glomerulopathies by inhibiting activation and proliferation of mesangial cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
42
0
4

Year Published

2002
2002
2011
2011

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 41 publications
(6 reference statements)
1
42
0
4
Order By: Relevance
“…Dietary fish oil supplementation has been shown to reduce progression of renal disease among patients with IgA nephropathy (22 ) and to suppress mesangial cell activation and proliferation in animal models (23 ). PUFAs may reduce inflammation through several possible pathways, such as reduction of nitric oxide (24 ), downregulation of TNF-␣ (25 ), and modulation of protein kinases (26 ).…”
Section: Discussionmentioning
confidence: 99%
“…Dietary fish oil supplementation has been shown to reduce progression of renal disease among patients with IgA nephropathy (22 ) and to suppress mesangial cell activation and proliferation in animal models (23 ). PUFAs may reduce inflammation through several possible pathways, such as reduction of nitric oxide (24 ), downregulation of TNF-␣ (25 ), and modulation of protein kinases (26 ).…”
Section: Discussionmentioning
confidence: 99%
“…In cultured MCs, we previously demonstrated that n-3 fatty acids block growth factor-stimulated mitogenesis through inhibition of ERK activation, reduction of cyclin E kinase activity, and induction of the cell cycle inhibitor p21 (78). In the antithymocyte serum model of mesangioproliferative glomerulonephritis, we demonstrated that n-3 fatty acids inhibit MC activation and proliferation, reduce proteinuria, and decrease histologic evidence of acute glomerular damage (22).…”
mentioning
confidence: 83%
“…In addition to IgA nephropathy, n-3 fatty acids have been used to treat a variety of inflammatory and autoimmune conditions (8,36,51). Potential mechanisms underlying this protective effect have not been well-established (22).…”
mentioning
confidence: 99%
“…Semiquantitative morphologic studies of glomerular lesions were performed on 25 glomeruli randomly selected from each specimen by one of the authors, each author being unaware of the origins of the slides. The degree of glomerular mesangial cell and/or matrix expansion was graded according to the percentage of glomerular involvement as described previously (16) using the following criteria: 0 ϭ normal glomerular cellularity with no significant mesangial expansion; 1ϩ ϭ mesangial cell and/or matrix expansion involving Ͻ25% of the glomerular area; 2ϩ ϭ mesangial cell and/or matrix expansion involving 26 to 50% of the glomerular area; 3ϩ ϭ mesangial cell and/or matrix expansion involving 51 to 75% of the glomerular area; and 4ϩ ϭ diffuse (Ͼ75% of the glomerular area) mesangial cell and/or matrix expansion or a glomerulus showing basement membrane disruption and/or mesangiolysis.…”
Section: Renal Morphologymentioning
confidence: 99%